Ocean Currents May Influence the Endolithic Bacterial Composition in Coral Skeletons - Liu, Po-Yu; Yang, Sung-Yin; Lu, Chih-Ying; Wada, Naohisa; De Palmas, Stéphane; Yeh, Shu-Shuo; Yamashiro, Hideyuki; Tang, Sen-Lin; Yang, Shan-Hua (Frontiers in Marine Science, 2022)
Coral endolithic microbes can be an important nutrients support for hosts while under stresses. Previous studies have found that the endolithic microbial composition of a single coral species can be biogeographical diverse. However, the potential environmental factors, such as salinity, temperature, pH, and nutrient, that might influence the composition of the endolithic microbes remain unclear. In this study, we used both amplicon sequence variants (ASV) and a kmer-based taxonomic unit (KTU) to characterize the endolithic bacterial constitution of Isopora spp. located in the western Pacific Ocean—where it is subjected to the Kuroshio Current (in Okinawa, Japan and Green Island, Taiwan)—and the South China Sea (Dongsha Atoll). The endolithic bacterial community compositions showed a significant geographical difference, and we suggest that the ocean current and primary productivity are the most essential environmental factors influencing the bacterial communities in the skeleton of Isopora spp. In addition, our results showed that, technically, compared to ASV, bacterial composition based on KTU avoids extreme data, making it a suitable tool for explaining the associations between microbes and environmental factors.